METAL COATED SUBSTRATES, INTERPOSERS AND METHODS FOR THEIR PRODUCTION - Patent application

The metallized substrate, with a conductive seed layer and a metal layer, addresses the thermal and adhesion limitations of traditional interconnects, enhancing thermal conductivity and reducing CTE mismatches for improved performance in high-performance electronic devices.

JP2025513680APending Publication Date: 2025-04-30KUPRION INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024548747
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-18
Filing Date
2023-02-15
Publication Date
2025-04-30

AI Technical Summary

Technical Problem

Current interconnects in electronic assemblies, such as those made from epoxy or solder, face limitations including limited thermal conductivity, insufficient thermal stability, and coefficient of thermal expansion (CTE) mismatches, which are particularly problematic in high-performance electronic devices with significant thermal loads.

Method used

A metallized substrate is developed, featuring a metal layer bound by a seed layer. The seed layer is initially formed on a non-conductive substrate and made electrically conductive through mechanical polishing. This substrate is particularly suitable for ceramic and glass substrates and can be used in various electronic assemblies, offering improved thermal conductivity and adhesion.

Benefits of technology

The metallized substrate enhances thermal conductivity, improves adhesion, and reduces CTE mismatches, leading to more robust and efficient interconnects in high-performance electronic devices. This solution addresses the limitations of traditional interconnect materials by providing a more effective thermal management system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025513680000001_ABST
    Figure 2025513680000001_ABST
Patent Text Reader

Abstract

The substrate may be metallized by introducing a seed layer onto the base substrate, mechanically polishing the seed layer, and forming a metal layer on the seed layer after mechanical polishing. The base substrate may include a ceramic, such as silicon nitride or aluminum nitride, a polymer, silicon, a metal, or a glass. The seed layer may optionally be made electrically conductive by mechanically polishing the initially non-conductive seed layer. The metal layer may be formed by depositing a metal nanoparticle composition onto the seed layer after mechanical polishing, and consolidating the metal nanoparticles in the metal nanoparticle composition, such as by a hot pressing operation. The metal nanoparticle composition may contain one or more additives that facilitate CTE matching of the metal layer to the base substrate.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] Modern electronic assemblies include numerous interconnects between various board components. The purpose of a given interconnect may be thermal, electrical, or structural in nature. Conventional interconnects are typically made from epoxy or tin- and / or lead-based solders due to their relatively low processing temperatures and low material and processing costs. Unfortunately, these materials are not ideally suited for some applications, especially new high performance electronics with large thermal loads, and as a result, current interconnects may exhibit several drawbacks and limitations.

[0002] Most electronics made today are manufactured using printed circuit board (PCB) technology, which may include several interconnects within it. The term "printed circuit board" is somewhat of a misnomer, given that most boards are not strictly printed, but instead utilize photolithography to pattern the desired conductive circuit patterns (conductive traces) from a copper sheet bonded to a substrate. The copper sheet is first bonded to an FR4 or similar fiberglass epoxy laminate, and then most of the copper is etched away to leave one or more conductive traces on the substrate in the desired pattern. In this process, up to 90% of the copper sheet may be etched away. While the etched copper may be salvaged, the etching process is time consuming, labor intensive, and may generate excessive amounts of hazardous waste. Most printed circuit boards are multi-layered, and the process must be repeated for each board layer. To further complicate matters, the low thermal conductivity of fiberglass epoxy substrates can be problematic in a variety of ways. Other types of substrates are of interest, but processing issues with these alternative substrates have yet to be universally resolved. In certain embodiments, as discussed further below, mismatch of the coefficient of thermal expansion (CTE) between the substrate and other components in the electrical interconnect, including the heat dissipation system, can be an issue.

[0003] The ongoing demand for reduced chip size, increased functionality, and improved performance all on smaller footprints continues to drive the need for heterogeneous integration in modern microelectronic components and systems. These developments are driven by various packaging and electrical interconnect technologies, such as wafer level fan out (WLFO), embedded multi-die interconnect bridge (EMIB), and interposer technologies. Interposers continue to be important for advanced electronic systems, such as 2.5D and 3D integrated circuits and system-in-package (SIP) applications, given the proven advantages of interposers with through-surface vias (TSVs).

[0004] Interposers are becoming increasingly prevalent as components within printed circuit boards (e.g., incorporated within system-in-package (SIP) and system-on-chip (SOC) configurations) to establish electrical and / or thermal transfer between various electronic components within the printed circuit board. Interposers commonly used for packaging applications fall into three main categories: silicon, organic (polymer), and glass. Each of these interposer material classes faces unique challenges with respect to electrical, mechanical, and thermal properties for producing high performance electronic devices. That is, as with other types of interconnects currently used in printed circuit boards, there are issues associated with the current class of interposers, such as limited thermal conductivity and / or poor bonding to metal components. CTE (coefficient of thermal expansion) mismatch in one or more interconnects can similarly result in thermo-mechanical stresses during repeated heating and cooling cycles. For interposers with large surface areas, the effects of CTE mismatch can be particularly problematic.

[0005] Silicon interposers have long played a key role in 2.5D and 3D IC chip integration due to their high fine pitch density and TSV formation capabilities. Silicon is a proven technology, used commercially in several high performance computing systems, and is currently favored in platforms using heterogeneous integration. However, silicon technology faces performance limitations caused by TSV profiles and microfluidic thermal design changes resulting from the need to mitigate thermal issues. High cost is another key challenge to overcome for continued market adoption. For example, when used within a device, silicon interposers can add as much as $30 for a medium size chip and even exceed $100 for larger size chips. Cost considerations have limited silicon interposers to high speed networking and server chip applications where the cost is lower than the driver.

[0006] Organic interposers are one alternative that is being explored to reduce costs and provide advantageously low dielectric constants. Organic interposers offer lower material costs and feature a well-established supply chain and the ability to be manufactured using conventional processes such as wet etching. The main challenge with organic interposers is their limited stiffness, especially for very thin substrates. Organic interposers also lack the ability to achieve the fine pitch densities possible with silicon and glass interposers. Organic interposers are currently well suited for applications such as logic memory integration, large central processing unit (CPU) / graphics processing unit (GPU), high performance radio frequency applications, and certain types of application specific integrated chips (ASICs), but in some cases can be used for other applications.

[0007] Glass interposers are a logical low-cost, high-performance alternative interposer technology that promises higher interconnect density than organic interposers and significantly lower cost compared to silicon interposers with similar interconnect density. Thus, glass interposers are increasingly being adopted in ultra-high pitch density applications, such as communications, networking and signal processing and testing, high-bandwidth memory (HBM), high-performance computing, and radio frequency (RF) technology. In addition, glass interposers are increasingly being adopted in low-cost packaging, such as micro-electromechanical systems (MEMS), sensors, power, and analog devices. In addition to lower cost, glass interposers are also available in large panel form. Key challenges associated with glass interposers include surface defects during manufacturing, which can lead to cracks and poor thermal conductivity. In addition, due to the large CTE mismatch between glass and conductive materials such as copper, there are limitations to the effective diameter achievable for through glass vias (TGVs), which effectively precludes the use of larger vias. Furthermore, glass interposers are expected to be a readily available solution to address current and future needs in the electronics industry.

[0008] With the proliferation of developments such as the Internet of Things (IoT), connected and autonomous vehicles, and similar devices, the challenge of processing and communicating high bandwidth data in combination with high performance electronic systems is becoming increasingly important. Interposers can be used in several different types of electronic systems, but the above is the main driver of the interposer market, as chip scaling is reaching its economic limits and packaging is becoming a key focus for advancing electronics at the chip scale. The continued growth of interposer technology depends on addressing the challenges, performance, and cost barriers induced by the interposer material itself in these and other applications. [Brief description of the drawings]

[0009] The following figures are included to illustrate certain aspects of the present disclosure and should not be viewed as exclusive embodiments. The disclosed subject matter is capable of significant modification, alterations, combinations, and equivalents in form and function, as will occur to those skilled in the art and having the benefit of this disclosure. [Figure 1] FIG. 1 is a diagram of the proposed structure of a metal nanoparticle having a surfactant coating thereon. [Diagram 2] FIG. 1 is a diagram of the proposed structure of a metal nanoparticle having a surfactant coating thereon. [Diagram 3] FIG. 1 is a diagram of a metallized substrate of the present disclosure. [Figure 4A] 1A and 1B are images of a glass substrate coated with a seed layer containing copper particles before and after polishing, respectively. [Figure 4B] 1A and 1B are images of a glass substrate coated with a seed layer containing copper particles before and after polishing, respectively. [Diagram 5] 1 is an image of a metallized glass substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] FIELD OF THE DISCLOSURE This disclosure relates generally to electronic assemblies, and more specifically to various types of metallized substrates suitable for use in electronic assemblies.

[0011] There are several types of interconnects that may be present in a printed circuit board or similar type of electronic assembly, including in an interposer. Traditionally, interconnects are formed of epoxy or solder. Despite their common use, epoxy and solder have limitations that are often not easily overcome with traditional materials. Limited thermal conductivity, poor thermal stability, and CTE (coefficient of thermal expansion) mismatch can often be problematic, for example, especially in high performance electronic devices with significant thermal loads.

[0012] Ceramic substrates, such as non-conductive ceramic materials, are desirable to incorporate into electronic assemblies as a result of their high thermal conductivity, excellent thermal stability, and good CTE matching with many semiconductor materials. Aluminum nitride and silicon nitride are just two examples of ceramic materials that are advantageous in this regard. However, direct metal bonding to such substrates can be problematic due to poor metal-ceramic adhesion. In addition, even if satisfactory metal adhesion can be achieved, CTE mismatch can still remain a problem. Similar problems can occur with other types of substrates other than ceramic as well.

[0013] The present disclosure describes a metallized substrate having a metal layer (metallization) bonded by a seed layer, which can be made electrically conductive by mechanical polishing. The seed layer is formed on a non-metallized (base) substrate in an initially non-conductive state, and can optionally be made electrically conductive in a simple manner, after which a metal layer can be formed or deposited on the seed layer, as described in more detail below. Although particularly suitable and advantageous for ceramic and glass substrates, both of which can be used in various types of electronic assemblies, the concepts disclosed herein may be equally applicable to other types of substrates, such as polymeric or silicon substrates. Illustrative examples of ceramic materials that can be metallized by application of the disclosure herein include, for example, aluminum oxide, aluminum nitride, silicon nitride, indium tin oxide, glass, silicon, and the like.

[0014] The seed layer may be formed on a particular substrate using an adhesive suitable for adhering to the particular type of substrate surface. Examples are provided below. Specifically, the substrate may first be coated with a thin layer of a seed layer precursor containing a non-conductive or low conductivity matrix material and dispersed metal particles. The dispersed metal particles may be micron-sized metal particles, metal nanoparticles, or any combination thereof. When metal nanoparticles in a metal nanoparticle paste formulation are used, the metal nanoparticle paste formulation may be blended with a non-conductive or low conductivity matrix material, and the resulting blend may be co-cured together. Depending on the surface chemistry of the base substrate, the seed layer may contain metal particles dispersed in an epoxy adhesive or liquid glass binder that may readily adhere to the surface of the base substrate after curing. The as-deposited seed layer after curing (e.g., at 80-100°C for 8-15 minutes) may be substantially an electrical insulator (electrically non-conductive) or very low conductivity, with the metal particles remaining largely isolated from one another. Although the as-deposited seed layer may be electrically non-conductive or of low conductivity, electrical conductivity may surprisingly be established by mechanically polishing the seed layer to form a polished seed layer prior to depositing a metal layer thereon. Establishing electrical conductivity in the seed layer by polishing may provide a dual advantage. First, enhanced bonding of the metallization layer to the polished seed layer may be realized. Second, the electrical conductivity of the conductive trace includes the combined conductivity of the seed layer and the metallization layer formed thereon. Thus, increasing the electrical conductivity of the seed layer may also increase the electrical conductivity of the resulting conductive trace. Finally, by making the seed layer electrically conductive, metallization strategies such as electroplating may be performed, which may in some cases be sufficient to form a metallization layer (e.g., instead of forming a metal trace by consolidating metal nanoparticles). In contrast, electroless plating or consolidating metal nanoparticles to form a metallization layer may be performed with a seed layer in either a conductive or non-conductive state.

[0015] Once the seed layer has been deposited and optionally made electrically conductive, it may be at least partially metallized to form a metal layer on the seed layer. Metallization may be performed by electroplating or electroless plating techniques, or more desirably using a metal nanoparticle composition. In contrast to plating techniques, a metal nanoparticle composition may be deposited and consolidated on the seed layer to form a thick metallized layer over substantially the entire surface of the seed layer, or only in specific locations using direct printing techniques. The thickness of the metallized layer achievable by metal nanoparticle consolidation may range from as little as about 10 microns to about 5000 microns (5 mm), or from about 10 microns to about 500 microns, or from about 500 microns to about 1000 microns, or from about 1000 microns to about 3000 microns. Plating techniques, in contrast, may result in very thin metallized layer thicknesses, such as layer thicknesses of about 50 microns or less, or about 10 microns or less. Direct printing techniques using metal nanoparticle compositions can result in conductive traces at specific locations on the surface of a substrate, whereas etching techniques are limited to forming conductive traces by etching the entire metallization layer at specific locations. Electrical isolation between conductive traces can be achieved by depositing a seed layer only at the locations where the conductive traces are to be formed, and / or by etching the seed layer after forming the conductive traces at the desired locations to limit the conductivity between the conductive traces.

[0016] As described in more detail below, the metal nanoparticle composition can be processed at relatively low temperatures (about 200°C to 250°C) to form the conductive traces or metallization layer in achieving the above. As an additional advantage, the metal nanoparticle composition can be formulated to provide a CTE match with the seed layer and base substrate, thereby promoting more robust performance of the deposited metal layer and / or conductive trace. As a metal for the conductive trace, copper is desirable due to its low cost and high electrical conductivity, but other metals can be used as well. Copper and other highly conductive metals, including mixtures or alloys thereof, can also be present as metal particles in the seed layer. Mixtures or alloys containing copper can be advantageous, for example, to provide improved oxidation resistance.

[0017] As described herein, low temperature processing of metal nanoparticles, including copper nanoparticles, is made possible by the enhanced activity of the metal nanoparticles compared to the corresponding bulk metal. As a result, the metal nanoparticles can be fused (consolidated) together at temperatures much lower than the metal melting point to provide at least a partial metal layer on the seed layer. The formation of bulk metals can be achieved at processing temperatures that would not be compatible with various electronic components when working with bulk metals directly in molten form. When metal nanoparticles are fused together, properties similar to those of the corresponding bulk metals can be achieved, but with the ability to tailor CTE or other properties by blending the metal nanoparticle composition.

[0018] Before discussing the embodiments of the present disclosure in more detail, a brief description of metal nanoparticles and metal nanoparticle compositions suitable for use in the present disclosure is first provided, with copper nanoparticles being representative of metal nanoparticles that may be present as the primary metal nanoparticles in a metal nanoparticle composition. Metal nanoparticles exhibit several properties that may be significantly different from those of the corresponding bulk metal. One property of metal nanoparticles that may be of particular importance is nanoparticle fusion or consolidation, which occurs at the melting temperature of the metal nanoparticles. As used herein, the term "melting temperature" refers to the temperature at which the metal nanoparticles liquefy, thereby giving the appearance of melting. As used herein, the terms "fusion," "sintering," and "consolidation" refer synonymously to the coalescence or partial coalescence of metal nanoparticles with each other to form a larger mass of bulk metal (sintered mass), thereby defining a bulk metal matrix, such as a bulk copper matrix. During nanoparticle fusion, the metal nanoparticles undergo consolidation to form a bulk metal matrix without passing through a liquid state.

[0019] As the size decreases, especially when the equivalent spherical diameter falls below about 200 nm, the temperature at which the metal nanoparticles coalesce drops dramatically from that of the corresponding bulk metal. For example, copper nanoparticles having a size of about 150 nm or less can have a melting temperature of about 240° C. or less, or about 220° C. or less, or about 200° C. or less, compared to the melting temperature of bulk copper of 1084° C. Some of the metal nanoparticles can be about 20 nm or less in size, which, among other things, can have a low melting temperature and facilitate the consolidation of larger metal nanoparticles. Thus, consolidation of the metal nanoparticles at the melting temperature can allow objects containing the bulk metal matrix, such as one or more interconnects, metal layers, and / or one or more conductive traces in an electronic assembly, to be manufactured at significantly lower processing temperatures than when working directly with the bulk metal itself as the starting material. When the bulk metal matrix is ​​formed, the melting point of the bulk metal matrix is ​​similar to that of the bulk metal itself and contains multiple grain boundaries. In addition, the bulk metal matrix may have defined nanoporosity that is not present in the corresponding bulk metal.

[0020] As used herein, the term "metal nanoparticles" refers to metal particles having a size of about 200 nm or less, without specific reference to the shape of the metal particle. As used herein, the term "copper nanoparticles" refers to metal nanoparticles made of copper or primarily copper.

[0021] As used herein, the term "micron-sized metal particles" refers to metal particles that are greater than or equal to about 250 nm in size in at least one dimension, without particular reference to the shape of the metal particles.

[0022] The terms "consolidate," "consolidation," and other variations thereof are used interchangeably herein with the terms "fuse," "fuse," and other variations thereof.

[0023] As used herein, the terms "partially fused," "partially fused," and other derivatives and grammatical equivalents refer to the partial coalescence of metal nanoparticles together. Fully fused metal nanoparticles do not retain essentially the structural morphology of the original unfused metal nanoparticles (i.e., they resemble bulk metal with minimal grain boundaries), whereas partially fused metal nanoparticles retain at least a portion of the structural morphology of the original unfused metal nanoparticles. The properties of partially fused metal nanoparticles can be intermediate between the properties of the corresponding bulk metal and the properties of the original unfused metal nanoparticles.

[0024] A number of scalable processes have been developed to produce large quantities of metal nanoparticles within a target size range. Most typically, such processes to produce metal nanoparticles are carried out by reducing a metal precursor in the presence of one or more surfactants. The metal nanoparticles can then be isolated and purified from the reaction mixture by common isolation techniques and processed into a paste composition as needed.

[0025] Any suitable technique can be used to form the metal nanoparticles used in the metal nanoparticle compositions and processes described herein. Particularly easy metal nanoparticle manufacturing techniques are described in U.S. Patent Nos. 7,736,414, 8,105,414, 8,192,866, 8,486,305, 8,834,747, 9,005,483, 9,095,898, and 9,700,940, each of which is incorporated herein by reference in its entirety. As described therein, metal nanoparticles can be produced in a narrow size range by reducing a metal salt in a solvent in the presence of a suitable surfactant system, which can include one or more different surfactants. Further description of suitable surfactant systems is provided below. Without being bound by any theory or mechanism, it is believed that the surfactant system can mediate the nucleation and growth of metal nanoparticles, limit the surface oxidation of metal nanoparticles, and / or inhibit the metal nanoparticles from extensively agglomerating together before at least partially fusing together. Suitable organic solvents for solubilizing metal salts and forming metal nanoparticles can include, for example, formamide, N,N-dimethylformamide, dimethylsulfoxide, dimethylpropyleneurea, hexamethylphosphoramide, tetrahydrofuran, and glyme, diglyme, triglyme, and tetraglyme. Suitable reducing agents for reducing metal salts and promoting the formation of metal nanoparticles can include, for example, alkali metals (e.g., lithium naphthalide, sodium naphthalide, or potassium naphthalide) or borohydride reducing agents (e.g., sodium borohydride, lithium borohydride, potassium borohydride, or tetraalkylammonium borohydride) in the presence of a suitable catalyst.

[0026] 1 and 2 are diagrams of the probable structure of a metal nanoparticle with a surfactant coating thereon. As shown in FIG. 1, metal nanoparticle 10 includes metal core 12 and surfactant layer 14 overcoating metal core 12. Surfactant layer 14 can contain any combination of surfactants, as described in more detail below. Metal nanoparticle 20 shown in FIG. 2 is similar to that shown in FIG. 1, except that metal core 12 has grown around nucleus 21, which can be the same metal as that of metal core 12 or a different metal. Nucleus 21 is deeply embedded within metal core 12 in metal nanoparticle 20, and is therefore not believed to significantly affect the overall nanoparticle properties. In some embodiments, nucleus 21 can include a substance that is a grain growth inhibitor, which can be released when metal nanoparticles undergo compaction together. In some embodiments, the nanoparticles can have an amorphous morphology.

[0027] As described above, the metal nanoparticles have a surfactant coating on their surface, which contains one or more surfactants. The surfactant coating can be formed on the metal nanoparticles during the synthesis of the metal nanoparticles. The surfactant coating is generally lost during the consolidation of the metal nanoparticles when heated above the melting temperature. Forming a surfactant coating on the metal nanoparticles during their synthesis can desirably limit the ability of the metal nanoparticles to fuse together before heating above the melting temperature, limit the aggregation of the metal nanoparticles, and promote the formation of a population of metal nanoparticles with a narrow size distribution.

[0028] Copper can be a particularly desirable metal in embodiments of the present disclosure due to its low cost, strength, and excellent electrical and thermal conductivity values, as well as additional advantages that will be further addressed herein. Copper nanoparticles can be advantageous for use in embodiments of the present disclosure, but it should be understood that other types of metal nanoparticles can be used in alternative embodiments. Other metal nanoparticles that can be useful in electronic applications to form bulk metal matrices include, for example, aluminum nanoparticles, palladium nanoparticles, silver nanoparticles, gold nanoparticles, iron nanoparticles, cobalt nanoparticles, nickel nanoparticles, titanium nanoparticles, zirconium nanoparticles, hafnium nanoparticles, tantalum nanoparticles, and the like. Micron-sized particles of these metals can also be present in metal nanoparticle compositions containing metal nanoparticles, and in some cases can provide processing advantages.

[0029] In various embodiments, the surfactant system present in the metal nanoparticles can include one or more surfactants. The different properties of various surfactants can be used to adjust the properties of the metal nanoparticles. Factors that can be taken into consideration when selecting a surfactant or a combination of surfactants to include on the metal nanoparticles include, for example, the ease of dissipation of the surfactant from the metal nanoparticles during nanoparticle fusion, the nucleation and growth rate of the metal nanoparticles, the metal content of the metal nanoparticles, etc.

[0030] In some embodiments, an amine surfactant or a combination of amine surfactants, particularly an aliphatic amine, can be present on the metal nanoparticles. Amine surfactants may be particularly desirable for use with copper nanoparticles. In some embodiments, two amine surfactants can be used in combination with each other. In other embodiments, three amine surfactants can be used in combination with each other. In more specific embodiments, primary amines, secondary amines, and diamine chelators can be used in combination with each other. In even more specific embodiments, the three amine surfactants can include long chain primary amines, secondary amines, and diamines with at least one tertiary alkyl group nitrogen substituent. Further disclosure regarding suitable amine surfactants follows below.

[0031] In some embodiments, the surfactant system can include a primary alkylamine. In some embodiments, the primary alkylamine is a C2-C 18 In some embodiments, the primary alkylamine is a C7-C 10 In other embodiments, C5-C6 primary alkylamines can also be used. Without being bound by any theory or mechanism, it is believed that the exact size of the primary alkylamine can be balanced between being long enough to provide an effective reverse micelle structure during synthesis, being easily volatile, and / or being easy to handle during nanoparticle compaction. For example, primary alkylamines having more than 18 carbons may also be suitable for use in this embodiment, but may be more difficult to handle due to their waxy nature. In particular, C7-C 10 Primary alkyl amines can represent a good balance of desirable properties for ease of use.

[0032] In some embodiments, C2 to C 18The primary alkylamine can be, for example, n-hexylamine, n-heptylamine, n-octylamine, n-nonylamine, or n-decylamine. These are all linear primary alkylamines, but in other embodiments, branched primary alkylamines can also be used. For example, branched primary alkylamines can be used, such as 7-methyloctylamine, 2-methyloctylamine, or 7-methylnonylamine. In some embodiments, such branched primary alkylamines can be sterically hindered when they are attached to the nitrogen atom of the amine. Non-limiting examples of such sterically hindered primary alkylamines can include, for example, t-octylamine, 2-methylpentan-2-amine, 2-methylhexane-2-amine, 2-methylheptan-2-amine, 3-ethyloctane-3-amine, 3-ethylheptane-3-amine, 3-ethylhexane-3-amine, and the like. Additional branching can also be present. Without being bound by any theory or mechanism, it is believed that primary alkylamines can act as ligands in the metal coordination sphere, but can easily dissociate from the metal coordination sphere during compaction of the metal nanoparticles.

[0033] In some embodiments, the surfactant system can include a secondary amine. Secondary amines suitable for forming metal nanoparticles include linear, branched, or cyclic C4-C bonded to the nitrogen atom of the amine. 12 The secondary amines may include, but are not limited to, dihexylamine, diisobutylamine, di-t-butylamine, dineopentylamine, di-t-pentylamine, dicyclopentylamine, dicyclohexylamine, and the like. C4-C 12 Secondary amines outside the above range can also be used, however, such secondary amines may have undesirable physical properties such as low boiling points or waxy consistency that can complicate their handling.

[0034] In some embodiments, the surfactant system can include a chelating agent, particularly a diamine chelating agent. In some embodiments, one or both of the nitrogen atoms of the diamine chelating agent can be substituted with one or two alkyl groups. When two alkyl groups are present on the same nitrogen atom, the two alkyl groups can be the same or different. Furthermore, when both nitrogen atoms are substituted, the same alkyl group can be present or different alkyl groups can be present. In some embodiments, the alkyl group can be a C1-C6 alkyl group. In other embodiments, the alkyl group can be a C1-C4 alkyl group or a C3-C6 alkyl group. In some embodiments, the C3 or higher alkyl group can be linear or branched. In some embodiments, the C3 or higher alkyl group can be cyclic. Without being bound by any theory or mechanism, it is believed that the diamine chelating agent can promote the formation of metal nanoparticles by promoting the nucleation of the nanoparticles.

[0035] In some embodiments, suitable diamine chelating agents may include N,N'-dialkylethylenediamines, particularly C1-C4 N,N'-dialkylethylenediamines. Corresponding methylenediamine, propylenediamine, butylenediamine, pentylenediamine or hexylenediamine derivatives may also be used. The alkyl groups may be the same or different. C1-C4 alkyl groups that may be present may include, for example, methyl, ethyl, propyl, and butyl groups, or branched alkyl groups such as isopropyl, isobutyl, s-butyl, and t-butyl groups. Exemplary N,N'-dialkylethylenediamines that may be suitable for inclusion on the metal nanoparticles include, for example, N,N'-di-t-butylethylenediamine, N,N'-diisopropylethylenediamine, and the like.

[0036] In some embodiments, suitable diamine chelating agents may include N,N,N',N'-tetraalkylethylenediamines, particularly C1-C4N,N,N',N'-tetraalkylethylenediamines. Corresponding methylenediamine, propylenediamine, butylenediamine, pentylenediamine or hexylenediamine derivatives may also be used. The alkyl groups may similarly be the same or different and may include those mentioned above. Exemplary N,N,N',N'-tetraalkylethylenediamines that may be suitable for use in forming metal nanoparticles may include, for example, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, and the like.

[0037] Surfactants other than aliphatic amines can also be present in the surfactant system.In this regard, suitable surfactants can include, for example, pyridines, aromatic amines, phosphines, thiols, or any combination thereof.These surfactants can be used in combination with aliphatic amines, including those mentioned above, or can be used in surfactant systems that do not have aliphatic amines.Further disclosure regarding suitable pyridines, aromatic amines, phosphines, and thiols follows below.

[0038] A suitable aromatic amine is ArNR 1 R 2 where Ar is a substituted or unsubstituted aryl group and R 1 and R 2 are the same or different. R 1 and R 2 can be independently selected from H or an alkyl or aryl group containing 1 to about 16 carbon atoms. Exemplary aromatic amines that may be suitable for use in forming metal nanoparticles include, for example, aniline, toluidine, anisidine, N,N-dimethylaniline, N,N-diethylaniline, and the like. Other aromatic amines that can be used in conjunction with metal nanoparticles can be envisioned by one of ordinary skill in the art.

[0039] Suitable pyridines include both pyridine and its derivatives. Exemplary pyridines that may be suitable for inclusion on metal nanoparticles include, for example, pyridine, 2-methylpyridine, 2,6-dimethylpyridine, collidine, pyridazine, etc. Chelating pyridines, such as bipyridyl chelators, may also be used. Other pyridines that may be used with metal nanoparticles may be envisioned by those skilled in the art.

[0040] Suitable phosphines can have the formula PR3, where R is an alkyl or aryl group containing 1 to about 16 carbon atoms. The alkyl or aryl groups attached to the phosphorus center can be the same or different. Exemplary phosphines that can be present on the metal nanoparticles include, for example, trimethylphosphine, triethylphosphine, tributylphosphine, tri-t-butylphosphine, trioctylphosphine, triphenylphosphine, and the like. Phosphine oxides can be used as well. In some embodiments, surfactants containing two or more phosphine groups configured to form a chelating ring can also be used. Exemplary chelating phosphines can include, for example, bisphosphines such as 1,2-bisphosphine, 1,3-bisphosphine, and BINAP. Other phosphines that can be used in conjunction with the metal nanoparticles can be envisioned by one of skill in the art.

[0041] Suitable thiols can have the formula RSH, where R is an alkyl or aryl group having about 4 to about 16 carbon atoms. Exemplary thiols that can be present on the metal nanoparticles include, for example, butanethiol, 2-methyl-2-propanethiol, hexanethiol, octanethiol, benzenethiol, and the like. In some embodiments, surfactants containing two or more thiol groups configured to form a chelating ring can also be used. Exemplary chelating thiols can include, for example, 1,2-dithiols (e.g., 1,2-ethanethiol) and 1,3-dithiols (e.g., 1,3-propanethiol). Other thiols that can be used in conjunction with the metal nanoparticles can be envisioned by one of ordinary skill in the art.

[0042] The metal nanoparticles described herein above can be incorporated into various metal nanoparticle compositions to facilitate their distribution to form the connections or metal layers of the present disclosure. An exemplary disclosure directed to such metal nanoparticle compositions follows below. Copper nanoparticle compositions can be particularly useful for forming the metal layers of the present disclosure, especially in the presence of grain growth inhibitors or CTE modifiers for metal layers or metal components that may be exposed to high operating temperatures, especially repeated thermal cycles. The metal nanoparticle compositions can be further formulated to impart oxidation resistance in the metallization layer or conductive traces formed therefrom.

[0043] Metal nanoparticle paste compositions can be prepared by dispersing as-produced or isolated metal nanoparticles in an organic matrix containing one or more organic solvents and various other optional ingredients. As used herein, the terms "nanoparticle paste formulation" and "nanoparticle paste composition" are used interchangeably and refer synonymously to a fluid composition containing dispersed metal nanoparticles suitable for dispensing using a desired technique. Viscosity can vary over a wide range depending on the dispensing technique selected. The use of the term "paste" does not necessarily imply adhesive capabilities of the paste alone. Through judicious selection of organic solvents and other additives, loading of metal nanoparticles, etc., the distribution of metal nanoparticles to desired locations can be facilitated and the properties of the resulting metal matrix (layer) can be tailored.

[0044] During consolidation of the metal nanoparticles in the metal nanoparticle composition, cracking and shrinkage can sometimes occur. One way that the metal nanoparticle composition can promote a reduction in the occurrence and void formation of cracking, shrinkage, and the degree of occurrence after metal nanoparticle consolidation is by maintaining a high solids content. More specifically, in some embodiments, the metal nanoparticle composition can contain at least about 30% metal nanoparticles by weight, particularly about 30% to about 97% metal nanoparticles by weight of the composition, or about 50% to about 97% metal nanoparticles by weight of the composition, or about 70% to about 97% metal nanoparticles by weight of the composition. Furthermore, in some embodiments, in addition to the metal nanoparticles, a small amount (e.g., about 0.01% to about 15% by weight or about 35% by weight or about 60% by weight of the composition) of micron-sized metal particles can be present. Such micron-sized metal particles can desirably promote the fusion of the metal nanoparticles into a continuous mass, further reducing the occurrence of cracking and shrinkage. Instead of being liquefied and undergoing direct compaction, the micron-sized metal particles can simply bond together when in contact with liquefied metal nanoparticles that have been elevated above their melting temperature. In essence, the metal nanoparticles can act as a "glue" that bonds the micron-sized metal particles together. These factors can reduce porosity after the metal nanoparticles are fused together, as well as provide tuning of the CTE. The micron-sized metal particles can include the same or different metals as the metal nanoparticles, and suitable metals for the micron-sized metal particles can include, for example, copper, silver, gold, aluminum, tin, and the like. In some embodiments, micron-sized graphite particles can also be included. In some embodiments, carbon nanotubes and / or graphene can be included. Still other additives in the micron-sized range, such as diamond particles or cubic BN (boron nitride), can be included as well.

[0045] During consolidation, the copper matrix defined by the fused copper nanoparticles is characterized by very fine, uniformly distributed nanoporosity (typically 4-15%, mostly closed pores, with pore sizes ranging from about 100 nm to about 300 nm) that limits hot spots by ensuring uniform heat distribution across the interfaces. However, the nanoporosity may range from about 2% to about 15% (i.e., about 85% to 98% high density fused copper nanoparticles, or other types of fused nanoparticles with closed pore nanoporosity and pore sizes ranging from about 50 nm to about 500 nm, or about 100 nm to about 300 nm, or about 150 nm to about 250 nm). Some copper bulk matrices described further below specify bulk copper matrices having a density of at least 90%. However, it should be understood that this value represents density values ​​that may be achieved for bulk copper matrices resulting from consolidation of copper nanoparticles and other types of metal nanoparticles, particularly densities in the range of about 85% to about 98%. Thus, the bulk copper matrix formed by consolidation of copper nanoparticles according to the present disclosure may have a density ranging from about 85% to about 98% of bulk copper. Nanoporosity may be within a similar range.

[0046] Micron-sized metal particles may be distinguished from grain growth inhibitors in the present disclosure because, due to their relatively large size, they are not easily incorporated within the grain boundaries between compacted metal nanoparticles. Specific examples of grain growth inhibitors or precursors thereof suitable for use in the present disclosure are discussed in more detail below.

[0047] The reduction of cracking and void formation during metal nanoparticle consolidation can also be promoted by judicious selection of the solvent forming the organic matrix. A tailored combination of organic solvents can desirably reduce the incidence of cracking and void formation. More specifically, organic matrices containing one or more hydrocarbons (saturated, monounsaturated, polyunsaturated (two or more double bonds) or aromatic), one or more alcohols, one or more amines, and one or more organic acids can be particularly effective for this purpose. In some embodiments, one or more esters and / or one or more anhydrides may be included. Without being bound by any theory or mechanism, it is believed that this combination of organic solvents can promote the removal and sequestering of surfactant molecules surrounding the metal nanoparticles during consolidation so that the metal nanoparticles can more easily fuse together. More specifically, it is believed that the hydrocarbon and alcohol solvents can passively solubilize surfactant molecules that are liberated from the metal nanoparticles by Brownian motion, reducing the ability of the surfactant molecules to reattach to the metal nanoparticles. In cooperation with the passive solubilization of the surfactant molecules, the amine solvents and organic acid solvents can actively sequester the surfactant molecules through chemical interactions such that they are no longer available to recombine with the metal nanoparticles.

[0048] Further adjustments to the solvent composition can be made to reduce the rapid volume shrinkage that occurs during surfactant removal and metal nanoparticle consolidation. Specifically, two or more members of each class of organic solvent (i.e., hydrocarbons, alcohols, amines, and organic acids) can be present in the organic matrix, with the members of each class having boiling points that are separated from one another by a set temperature. For example, in some embodiments, the various members of each class can have boiling points that are separated from one another by about 5°C to about 50°C or about 20°C to about 50°C. By using such a solvent mixture, the various components of the solvent mixture can be gradually removed over a wide range of boiling points (e.g., about 50°C to about 200°C), thereby minimizing rapid volume changes due to rapid loss of solvent during metal nanoparticle consolidation.

[0049] In some embodiments, at least a portion of the one or more organic solvents can have a boiling point of about 100° C. or higher. In some embodiments, at least a portion of the one or more organic solvents can have a boiling point of about 200° C. or higher. In some embodiments, the one or more organic solvents can have a boiling point in the range of about 50° C. to about 250° C. In other embodiments, the one or more organic solvents can have a boiling point in the range of about 100° C. to about 350° C. or about 100° C. to about 370° C. The use of high boiling organic solvents can desirably increase the pot life of the metal nanoparticle composition and limit the rapid loss of solvent that can lead to cracking and void formation during metal nanoparticle consolidation. In some embodiments, at least one of the organic solvents can have a boiling point higher than the boiling point of the surfactant associated with the metal nanoparticles. Thus, the surfactant can be removed from the metal nanoparticles by evaporation before removal of the organic solvent is performed.

[0050] In some embodiments, the organic matrix can contain one or more alcohols. In various embodiments, the alcohols can include monohydric alcohols, diols, triols, glycol ethers (e.g., diethylene glycol and triethylene glycol), alkanolamines (e.g., ethanolamine, triethanolamine, etc.), or any combination thereof. In some embodiments, one or more hydrocarbons can be present in combination with one or more alcohols. As discussed above, it is believed that alcohol and hydrocarbon solvents can passively promote the solubilization of surfactants because they are removed from the metal nanoparticles by Brownian motion and have limited reassociation with the metal nanoparticles. Furthermore, hydrocarbon and alcohol solvents are only weakly coordinated to the metal nanoparticles, and therefore do not simply replace the substituted surfactant in the nanoparticle coordination sphere. Illustrative, but non-limiting examples of alcohol and hydrocarbon solvents that may be present include, for example, light aromatic petroleum distillates (CAS 64742-95-6), hydrotreated light petroleum distillates (CAS 64742-47-8), tripropylene glycol methyl ether, ligroin (CAS 68551-17-7, C 10 ~C 13 Mixtures of alkanes), diisopropylene glycol monomethyl ether, diethylene glycol diethyl ether, 2-propanol, 2-butanol, t-butanol, 1-hexanol, 2-(2-butoxyethoxy)ethanol, and terpineol. In some embodiments, polyketone solvents can be used as well.

[0051] In some embodiments, the organic matrix may contain one or more amines and one or more organic acids. In some embodiments, the one or more amines and one or more organic acids may be present in an organic matrix that also includes one or more hydrocarbons and one or more alcohols. As discussed above, it is believed that the amines and organic acids may actively sequester surfactants that have been passively solubilized by the hydrocarbon and alcohol solvents, thereby making the surfactants unavailable for reassociation with the metal nanoparticles. Thus, organic solvents containing a combination of one or more hydrocarbons, one or more alcohols, one or more amines, and one or more organic acids may provide synergistic benefits for promoting compaction of metal nanoparticles. Illustrative, but non-limiting examples of amine solvents that may be present include, for example, tallow amine (CAS 61790-33-8), alkyl (C8-C9), tallow amine (CAS 61790-33-8 ... 18 )Unsaturated amines (CAS 68037-94-5), di(hydrogenated tallow)amine (CAS 61789-79-5), dialkyl (C8-C 20 )Amine (CAS 68526-63-6), Alkyl (C 10 ~C 16 ) Dimethylamine (CAS 67700-98-5), Alkyl (C 14 ~C 18 ) dimethylamine (CAS 68037-93-4), dihydrogenated tallow methylamine (CAS 61788-63-4), and trialkyl (C6-C 12 ) amine (CAS 68038-01-7). Illustrative, but non-limiting examples of organic acid solvents that may be present in the nanoparticle paste composition include, for example, octanoic acid, nonanoic acid, decanoic acid, caprylic acid, pelargonic acid, undecylic acid, lauric acid, tridecylic acid, myristic acid, pentadecanoic acid, palmitic acid, margaric acid, stearic acid, nonadecylic acid, alpha-linolenic acid, stearidonic acid, oleic acid, and linoleic acid.

[0052] In some embodiments, the organic matrix can include two or more hydrocarbons, two or more alcohols, two or more amines, and two or more organic acids. For example, in some embodiments, each class of organic solvent can have two or more members, or three or more members, or four or more members, or five or more members, or six or more members, or seven or more members, or eight or more members, or nine or more members, or ten or more members. Furthermore, the number of members in each class of organic solvent can be the same or different. Specific advantages of using multiple members of each class of organic solvent are described below.

[0053] One particular advantage of using multiple members within each class of organic solvents can include the ability to provide a wide range of boiling points in the nanoparticle paste composition. By providing a wide range of boiling points, the organic solvent can be gradually removed as the temperature increases, while affecting the compaction of the metal nanoparticles, thereby limiting volumetric shrinkage and favoring cracking. By gradually removing the organic solvent in this manner, less temperature control may be required to affect slow solvent removal than if a single solvent with a narrow boiling range were used. In some embodiments, members within each class of organic solvents can have a boiling window ranging from about 50°C to about 200°C, or from about 50°C to about 250°C, or from about 100°C to about 200°C, or from about 100°C to about 250°C. Higher boiling solvents can be used as well. In more specific embodiments, the various members of each class of organic solvents can each have boiling points that are at least about 5°C apart, or at least about 10°C apart, or at least about 20°C apart, e.g., from about 5°C to about 25°C, or from about 10°C to about 35°C, or from about 20°C to about 50°C. More specifically, in some embodiments, each hydrocarbon can have a boiling point that differs from other hydrocarbons in the organic matrix by about 20°C to about 50°C, each alcohol can have a boiling point that differs from other alcohols in the organic matrix by about 20°C to about 50°C, each amine can have a boiling point that differs from other amines in the organic matrix by about 20°C to about 50°C, and each organic acid can have a boiling point that differs from other organic acids in the organic matrix by about 20°C to about 50°C. The more members of each class of organic solvents that are present, the smaller the difference between the boiling points will be. By making the difference between the boiling points smaller, the solvent removal can be made more continuous, thereby limiting the amount of volumetric shrinkage that occurs at each stage. When 4-5 or more members of each class of organic solvents are present, each having boiling points that are separated from one another within the above ranges (e.g., 4 or more hydrocarbons, 4 or more alcohols, 4 or more amines, and 4 or more organic acids; or 5 or more hydrocarbons, 5 or more alcohols, 5 or more amines, 5 or more organic acids), a reduced degree of cracking may occur.

[0054] In various embodiments, the metal nanoparticles used in the nanoparticle paste composition can be about 20 nm or less in size. In some embodiments, suitable metal nanoparticles can be up to about 75 nm in size, up to about 100 nm in size, up to about 150 nm in size, or up to about 200 nm in size. As discussed above, metal nanoparticles in the size range of about 20 nm or less have a melting temperature significantly lower than that of the corresponding bulk metal, and as a result can easily undergo compaction with each other. Therefore, in at least some embodiments, metal nanoparticles of about 20 nm or less in size can be combined with metal nanoparticles of 20 nm or more in size to facilitate tuning of the melting temperature. In some embodiments, metal nanoparticles of about 20 nm or less in size can have a melting temperature of about 220° C. or less (e.g., a melting temperature in the range of about 140° C. to about 220° C.) or a melting temperature of about 200° C. or less, which can provide the above-mentioned advantages. In some embodiments, at least a portion of the metal nanoparticles can be about 10 nm or less in size, or about 5 nm or less in size. In some embodiments, at least a portion of the metal nanoparticles can range from about 1 nm in size to about 20 nm in size, or from about 1 nm in size to about 10 nm in size, or from about 1 nm in size to about 5 nm in size, or from about 3 nm in size to about 7 nm in size, or from about 5 nm in size to about 20 nm in size. Any of the above size ranges can be combined with metal nanoparticles of about 30 nm or more in size, or about 50 nm or more in size, or about 75 nm or more in size, or about 100 nm or more in size, or about 150 nm or more in size. In some embodiments, substantially all of the metal nanoparticles can be present within these size ranges. In some embodiments, larger metal nanoparticles can be combined with metal nanoparticles of about 20 nm or less in size in the metal nanoparticle paste composition. For example, in some embodiments, metal nanoparticles ranging from about 1 nm to about 10 nm in size or from about 5 nm to about 20 nm in size can be combined with metal nanoparticles ranging from about 25 nm to about 50 nm in size, or from about 25 nm to about 100 nm in size, or from about 30 nm to about 80 nm in size.In other embodiments, smaller metal nanoparticles are not necessarily present, and the metal nanoparticles may be in the range of about 30 nm or more in size, or about 50 nm or more in size, or about 75 nm or more in size, or about 100 nm or more in size, or about 150 nm or more in size, for example, about 30 nm to about 100 nm, or about 75 nm to about 150 nm, or about 125 nm to about 200 nm in size. More efficient packing of metal nanoparticles during consolidation may be achieved by using metal nanoparticles of two different size ranges. As discussed further below, in some embodiments, micron-sized metal particles or nanoscale particles may also be included in the metal nanoparticle composition. Although larger metal nanoparticles and micron-sized metal particles may not be liquefiable at the low temperatures of their smaller counterparts, they can still be consolidated when in contact with smaller metal nanoparticles that have formed a liquefied-like state at or above their melting temperatures, as generally discussed above. When smaller and larger metal nanoparticles are used in combination with each other, the smaller and larger metal nanoparticles can be combined in any ratio.

[0055] In addition to the metal nanoparticles and organic solvent, other additives can also be present in the metal nanoparticle paste composition. Such additional additives can include, for example, rheology control aids, thickeners, micron-sized conductive additives, nanoscale conductive additives, CTE adjusters, and any combination thereof. Chemical additives can also be present. As discussed below, it can be particularly advantageous to include micron-sized conductive additives, such as micron-sized metal particles. In some cases, it may be desirable to include nanoscale or micron-sized diamond or other thermal conductive additives.

[0056] In some embodiments, the metal nanoparticle composition can contain about 0.01% to about 15% by weight of micron-sized metal particles, or about 1% to about 10% by weight of micron-sized metal particles, or about 1% to about 5% by weight of micron-sized metal particles. The micron-sized metal particles can also be present in the metal nanoparticle composition in an amount of about 10% to about 35% by weight, or about 15% to about 35% by weight, or about 20% to about 35% by weight, or about 25% to about 35% by weight. The inclusion of micron-sized metal particles in the metal nanoparticle composition can desirably reduce the incidence of cracking that occurs during consolidation of the metal nanoparticles when forming the metal layer or conductive traces in the present disclosure. Without being bound by any theory or mechanism, it is believed that the micron-sized metal particles can become consolidated with each other when the metal nanoparticles form a liquefied-like state and form a temporary liquid coating on the surface of the micron-sized metal particles. In some embodiments, the micron-sized metal particles can range in size from about 500 nm to about 100 microns in at least one dimension, or from about 500 nm to about 10 microns in at least one dimension, or from about 100 nm to about 5 microns in at least one dimension, or from about 100 nm to about 10 microns in at least one dimension, or from about 100 nm to about 1 micron in at least one dimension, or from about 1 micron to about 10 microns in at least one dimension, or from about 5 microns to about 10 microns in at least one dimension, or from about 1 micron to about 100 microns in at least one dimension. The micron-sized metal particles can contain the same metal as the metal nanoparticles, or can contain a different metal. This allows for the production of metal alloys by including micron-sized metal particles in metal nanoparticles having a different metal than the metal of the metal nanoparticles.Suitable micron-sized metal particles can include, for example, Cu particles, Ni particles, Al particles, Fe particles, Co particles, Mo particles, Ag particles, Zn particles, Sn particles, Au particles, Pd particles, Pt particles, Ru particles, Mn particles, Cr particles, Ti particles, V particles, Mg particles, or Ca particles. Non-metallic particles, such as, for example, Si micron-sized particles and B micron-sized particles, can be used as well. In some embodiments, the micron-sized metal particles can be in the form of metal flakes, such as, for example, high aspect ratio copper flakes. That is, in some embodiments, the metal nanoparticle composition described herein can contain a mixture of copper nanoparticles and high aspect ratio copper flakes or copper nanoparticles and other micron-sized copper particles. Specifically, in some embodiments, the metal nanoparticle composition can contain about 30% to about 97% by weight of copper nanoparticles and about 0.01% to about 15% by weight or 0.1% to 30% by weight of high aspect ratio copper flakes or other micron-sized copper particles. The high aspect ratio copper flakes, according to some embodiments, can be in the form of nanoparticles.

[0057] Other micron-sized metal particles that can be used equivalently to the high aspect ratio metal flakes include, for example, metal nanowires and other high aspect ratio particles, which can be up to about 300 microns in length. The ratio of metal nanoparticles to metal nanowires can be in the range of about 10:1 to about 40:1, according to various embodiments. Suitable nanowires can have lengths of, for example, about 5 microns to about 50 microns, and diameters of about 100 nm to about 200 nm.

[0058] In some embodiments, nanoscale conductive additives can also be present in the metal nanoparticle composition. These additives can desirably provide additional structural reinforcement and reduce shrinkage during metal nanoparticle consolidation. Furthermore, the inclusion of nanoscale conductive additives can increase electrical and thermal conductivity values ​​that can approach or even exceed the electrical or thermal conductivity values ​​of the corresponding bulk metal after nanoparticle consolidation. In some embodiments, the nanoscale conductive additives can have a size in at least one dimension ranging from about 1 micron to about 100 microns, or from about 1 micron to about 300 microns. Suitable nanoscale conductive additives can include, for example, carbon nanotubes, graphene, other graphite-type materials, and the like. When present, the metal nanoparticle composition can contain about 1% to about 16% by weight of the nanoscale conductive additive, or about 1% to about 10% by weight of the nanoscale conductive additive, or about 1% to about 5% by weight of the nanoscale conductive additive.

[0059] Additional materials that may also be optionally present in the metal nanoparticle composition include, for example, flame retardants, UV protection agents, antioxidants, carbon black, graphite, fibrous materials (e.g., chopped carbon fiber materials), diamond, cubic BN, and the like.

[0060] Metal nanoparticle compositions suitable for use in the present disclosure can be formulated using any of the formulations described herein above, including those that further include a grain growth inhibitor, particularly a grain growth inhibitor that includes a metal. The grain growth inhibitor can be included in a suitable form such that it can enter the grain boundaries after nanoparticle compaction. If not included in a suitable form, ineffective grain growth inhibition can occur, even if the grain growth inhibitor otherwise includes a material that can provide grain growth inhibition.

[0061] In certain embodiments, metal nanoparticle compositions suitable for use in the present disclosure may include copper nanoparticles and a suitable amount of a grain growth inhibitor to prevent substantial grain growth upon heating of a bulk copper matrix formed from the copper nanoparticles. Various CTE modifiers may be present as well. A suitable amount of grain growth inhibitor and / or CTE adjuster may range from about 0.01% to about 15% by weight of the composition, according to various embodiments. The effective temperature ranges at which grain growth inhibitors may inhibit grain growth are discussed below.

[0062] Suitable grain growth inhibitors can be metal particles that are insoluble in the copper matrix. Suitable grain growth inhibitors can be heterogeneous nanoparticles with a size range of 25 nm or less or a size range of about 10 nm or less. It may be particularly desirable to include grain growth inhibitors containing metal, especially metal nanoparticles with a size of about 25 nm or less or about 10 nm or less, in the bulk copper matrix. The small nanoparticle size allows the grain growth inhibitor to easily access the grain boundaries. The inclusion of grain growth inhibitors restricts grain growth by interfaces or Zener pinning, ensuring that the nanograin structure is maintained even after long-term exposure to high temperatures, frequent temperature cycles, and thermal shocks. These actions can prevent further atomic diffusion and reorganization.

[0063] Suitable metals for the grain growth inhibitors may include, for example, Fe, Mn, Cr, Co, Ru, Si, V, W, Nb, Ta, Y, Zr, Hf, Be, Tl, Rh, Ir, Ti, Mo, Re, Al, alloys thereof, or any combination thereof, particularly nanoparticles containing one or more of these metals. Si is considered to be a metal for the purposes of this disclosure. The metal particles may be metal nanoparticles or micron-sized metal particles, according to various embodiments. Nanoparticles of these metals may be particularly suitable. Other suitable grain growth inhibitors may include, for example, carbides, nitrides, borides, silicides, or phosphides. Suitable borides may include, for example, Zr / Hf, V, or Nb / Ta. Any of the above metals may be suitable, although similar metals are suitable for carbides, nitrides, silicides, and phosphides. Other suitable phosphides may include covalent phosphides such as BP and SiP2, transition metal phosphides such as Fe3P, Fe2P, Ni2P, CrP, MnP, MoP, etc. Metal-rich phosphides such as these may be desirable due to their water insolubility, electrical conductivity, high melting point, thermal stability, hardness, and similar properties. Other suitable carbides include BC (B x C y Covalent carbides such as SiC (including non-stoichiometric carbides) and SiC, as well as transition metal carbides, which also exhibit high melting points, hardness, electrical conductivity, and similar properties. Graphene and other nanocarbon materials may also be effective grain growth inhibitors in some cases.

[0064] Suitable grain growth inhibitors may be included in the copper nanoparticle paste composition or in the bulk copper matrix obtained therefrom in an amount ranging from about 0.01% to about 15% by weight of the composition. In more specific embodiments, the grain growth inhibitor may be present in an amount ranging from about 0.01% to about 5% by weight, or from about 0.1% to about 0.5% by weight. Particular copper nanoparticle compositions may include up to about 12% by weight Al, or about 0.01 to 5% by weight Zr, or 0.01 to 5% by weight Zr / Hf. These particular grain growth inhibitors in the amounts mentioned may provide temperature stability up to about 940° C., 500° C., or 600° C., respectively. Aluminum may be advantageous in forming insoluble binary phases such as CuAl2 or Cu9Al4. Al2O3, including its nanoparticles, may be a suitable grain growth inhibitor and may impart improved oxidation resistance.

[0065] The grain growth inhibitor can be in various forms when incorporated / combined with the copper nanoparticles. In some embodiments, the grain growth inhibitor can be a nanoparticle itself, particularly having a size of about 25 nm or less, or about 10 nm or less. In other embodiments, the grain growth inhibitor can range in size from 10 nm to 100 nm, or from about 25 nm to about 100 nm.

[0066] When incorporated as nanoparticles, the reagents for forming grain growth inhibitors can be mixed with the reagents for forming copper nanoparticles (or other types of metal nanoparticles), which can then undergo co-reduction to simultaneously form copper nanoparticles and grain growth inhibitors. Suitable reagents for forming grain growth inhibitors can include, for example, nitrates, chlorides, bromides, or iodides of metals. Grain growth inhibitors can also constitute nanoparticle seeds for copper nanoparticles (or other metal nanoparticles) and then be incorporated into the bulk copper matrix obtained after copper nanoparticle fusion. Nanoparticle seeds suitable for becoming grain growth inhibitors can be made separately and combined with the reagents for forming copper nanoparticles, or such nanoparticle seeds can be formed simultaneously with the formation of copper nanoparticles. A carrier solvent can be used to disperse the reagents for forming nanoparticle seeds / grain growth inhibitors before dispersing with the copper nanoparticles or copper nanoparticle precursors.

[0067] Alternatively, the preformed grain growth inhibitor can be mixed with the preformed copper nanoparticles (or other metal nanoparticles) either before or after the copper nanoparticles are incorporated into the metal nanoparticle composition.

[0068] In yet another alternative embodiment, a trialkylaluminum compound (e.g., trimethylaluminum) may be incorporated into the metal nanoparticle composition. The trialkylaluminum may react during copper nanoparticle consolidation to release aluminum or aluminum compounds to the grain boundaries.

[0069] Further alternatively, a salt that forms a grain growth inhibitor after reduction can be mixed within the metal nanoparticle composition and then undergo reduction to form the grain growth inhibitor during consolidation of the metal nanoparticles. A carrier solvent can be used to facilitate mixing with the metal nanoparticle composition.

[0070] In yet another embodiment, NaReO4 can be incorporated into the grain growth inhibitor. This salt is compatible with both aqueous and non-aqueous solvent conditions (including glyme solvent mixtures) and the same amines that can be used in forming copper nanoparticles. Reducing agents such as NaBH4, CaH2, hydrazine, organomagnesium or organosodium compounds, or redAl can be used to affect reduction.

[0071] CTE tuning in metal nanoparticle compositions or metallized layers obtained therefrom can be achieved by adding low CTE materials in the form of small particles (e.g., platelets, fibers, wires, etc. in the 0.5-250 micron range) to the metal nanoparticle composition. Examples include, but are not limited to, diamond, BN, SiC, AlN, graphite, carbon nanotubes, graphene, etc. Preferably, CTE tuning can be achieved using materials with high thermal conductivity, although silica and other oxides with negative thermal expansion may be suitable as well. The addition of micron-sized metal particles allows for upward tuning. High aspect ratio particles may further help increase mechanical strength. CTE tuning, also referred to as CTE matching in this disclosure, may refer to two CTE values ​​that differ from each other by about 20% or less, about 15% or less, about 10% or less, about 5% or less, or about 1% or less.

[0072] Thus, the present disclosure provides a metallized substrate, which may be an interposer for incorporating electronic components, comprising a base substrate, a seed layer directly bonded to the base substrate, and a metal layer formed on at least a portion of the seed layer. The seed layer may comprise a non-conductive matrix material and a plurality of metal particles, and may optionally be electrically conductive. The metal particles in the seed layer may be the same or different from the metal present in the metal layer. The metal particles in the seed layer may be in the micron size range or larger. The size of the metal particles in the seed layer may determine, at least in part, the thickness of the seed layer, as well as other seed layer properties. In a more specific example, the metallized substrate of the present disclosure may comprise a base substrate and a seed layer directly bonded to the base substrate, the seed layer being mechanically polished and comprising a non-conductive matrix material and a plurality of metal particles, and optionally the seed layer being electrically conductive, and the metal layer formed on at least a portion of the seed layer.

[0073] FIG. 3 is a diagram of a metallized substrate of the present disclosure. As shown, the metallized substrate 100 includes a base substrate 102 having a seed layer 104 thereon. The seed layer 104 includes a matrix material 105 and metal particles 106 therein. Exemplary examples of the matrix material 105, base substrate 102, and metal particles 106 are discussed further herein. A metal layer 108, preferably formed from a metal nanoparticle composition, may be deposited on at least a portion of the seed layer 104 and CTE matched thereto. The metal layer 108 may be a metallized layer that is subsequently etched to define conductive traces on the base substrate 102, or conductive traces printed directly on the seed layer 104 using the metal nanoparticle composition. Although the seed layer 104 and metal layer 108 are shown as having a sharp interface between the two, it should be understood that at least partial intermixing may occur between the seed layer 104 and the metal layer 108, resulting in an intermixed zone of about 1-10 microns between the two.

[0074] The base substrate suitable for use in the present disclosure is not believed to be particularly limited, provided that the seed layer can be sufficiently adhered to the base substrate upon curing of the seed layer precursor. In non-limiting examples, the base substrate can include ceramic, polymer, silicon, or glass. In other examples, the base substrate can include a metal or metal alloy (e.g., WCu, MoCu, Al, Ni, stainless steel, etc.) to which the metal layer will not adhere in the absence of the seed layer. Otherwise, metal substrates may be difficult to metallize due to their native oxide coating. In more specific examples, the base substrate can include a ceramic, such as, for example, aluminum nitride, silicon nitride, indium tin oxide, aluminum silicon carbide, or any combination thereof.

[0075] AlN (thermal conductivity up to 260 W / m·K) and SiN (thermal conductivity up to 90 W / m·K) are both highly thermally conductive and electrically insulating ceramic substrates that may be particularly suitable for use in the present disclosure. By being able to effectively form a metal layer on AlN or SiN, an increase in thermal conductivity of three orders of magnitude greater than that provided by FR4 and similar fiberglass substrates may be realized. Increased thermal resistance may be realized as well. The high thermal conductivity of these ceramic substrates may promote good heat dissipation within electronic components, thereby preventing premature burnout and other types of damage that may occur as a result of thermal damage in PCBs or similar architectures.

[0076] Aluminum nitride (AlN) has a hexagonal crystal structure and is a covalent material. Sintering aids and hot pressing can be used to produce dense industrial grade materials for use as ceramic substrates. AlN is particularly stable to very high temperatures in inert atmospheres. In air, surface oxidation begins at 700°C or higher. A surface layer of aluminum oxide (5-10 nm thick) can form at higher temperatures and protect the material up to 1370°C. Above this temperature, bulk oxidation can occur. Aluminum nitride is stable up to 980°C in hydrogen and carbon dioxide atmospheres. The material dissolves slowly in mineral acids by grain boundary attack and in strong alkalis by attack on the aluminum nitride grains. The material hydrolyzes slowly in water. Thus, AlN can be a ceramic substrate that is particularly suitable for use in the present disclosure, given its high thermal conductivity and thermal stability under a range of conditions below the melting point of bulk copper.

[0077] AlN and SiN may be particularly suitable ceramic substrates due to their high thermal conductivity and low cost, although other ceramic substrates may also be suitable for use in the present disclosure. Non-limiting examples of other types of ceramic substrates suitable for use in the present disclosure include cubic BN (130 W / m K), BeO (330 W / m K), diamond (2300 W / m K), BAs (1300 W / m K), isotopically enriched cubic 10 BN and cubic 11 These may include, but are not limited to, BN (greater than 1600 W / m·K), Si (148 W / m·K), cubic C3N4, AlSiC, etc. AlN and / or SiN may also be mixed with any of the above ceramic materials in a suitable ceramic substrate.

[0078] Optionally, one or more vias may extend between the first and second sides of the base substrate. The vias may be at least partially filled with a thermally or electrically conductive material, and may optionally be further combined with a matrix material as discussed herein. Blind vias that do not completely penetrate the base substrate may be at least partially filled in a similar manner. Blind vias include grooves defined in the base substrate.

[0079] Any suitable technique may be utilized to form the ceramic substrate prior to depositing a metal layer thereon in accordance with the disclosure herein. Powder compaction or tape casting procedures may be used to form suitable ceramic substrates. Tape casting and the use of sintering aids, particularly fugitive sintering aids, may facilitate the formation of ceramic substrates having thicknesses as low as about 200 microns and sizes compatible with PCB manufacturing (e.g., 5" x 7" sheets). Particularly suitable ceramic substrates may be substantially planar so that they can be easily stacked in forming multi-layer PCBs.

[0080] A coating formulation (seed layer precursor) may be deposited on a base substrate, subsequently cured, and a metal layer may be deposited thereon. The seed layer precursor may include a non-conductive matrix material or matrix material precursor and a plurality of metal particles. The non-conductive matrix material may be selected to promote bonding with the particular type of substrate undergoing metallization according to the present disclosure. The metal particles in the seed layer precursor may be a plurality of micron-sized metal particles, such as copper powder. The matrix material or matrix material precursor may be a liquid glass binder (e.g., silane, silicate, or similar chemical), a polymer adhesive such as an epoxy, or any combination thereof. Curing of the matrix material or matrix material precursor may transform the non-conductive matrix material or matrix material precursor from an initial fluid state to a substantially non-fluid state, thereby defining a seed layer that is physically and / or chemically bonded to the surface of the substrate. In some embodiments, the non-conductive matrix material may bond the metal particles together in the seed layer.

[0081] Optionally, the seed layer precursor may further include an additive that improves compatibility between the non-conductive matrix material of the seed layer and the metal particles therein, such as by promoting covalent bond formation between the two. Increased interaction between the metal particles and the non-conductive matrix material may help prevent cracking under thermal stress. In some embodiments, the additive may include an amino group that may react with the surface of the metal particles and a silane group that may react with the non-conductive matrix material. That is, the additive may act as a bridging group between the metal particles and the hardened non-conductive matrix material. Thus, suitable additives include aminoalkyldialkoxysilanes, aminoalkyltrialkoxysilanes, or any combination thereof. Aminopropyltriethoxysilane (APTES) is a non-limiting example of a suitable additive that may be present.

[0082] Suitable techniques for applying the seed layer precursor to the base substrate are not considered to be particularly limited, and may include, but are not limited to, techniques such as spray-on, brush-on, dip coating, inkjet printing, stencil, spin-on coating, or similar application techniques.Unless otherwise indicated, all or a substantial portion of the surface of the base substrate may be coated with the seed layer.Directional deposition techniques for the seed layer precursor may also be suitably used.

[0083] The metal particles in the seed layer precursor may be the same as or different from the metal particles in the metal layer. For example, the metal particles in the seed layer precursor and the metal in the metal layer may both include copper. The metal in the metal layer may include a metal selected from any of the metal nanoparticle types mentioned above, and the metal particles in the seed layer precursor may be selected to match or be different from the metal that makes up the metal layer.

[0084] The amount of non-conductive matrix material or matrix material precursor to metal particles in the seed layer precursor can vary over a wide range. The selected range can be chosen so that the seed layer precursor can be distributed by a particular application technique. In non-limiting examples, the mass ratio of metal particles to non-conductive matrix material or matrix material precursor in the seed layer precursor or the seed layer resulting therefrom can range from about 1:1 to about 10:1, or from about 2:1 to about 6:1, or from about 2:1 to about 5:1, or from about 3:1 to about 4:1.

[0085] The layer thickness of the seed layer after curing can vary over a range of values ​​and can depend on the size of the metal particles present therein. In non-limiting examples, the seed layer can range from about 500 nm to about 50 microns thick, or about 1 micron to about 30 microns thick, or about 1 micron to about 20 microns thick, or about 5 microns to about 30 microns thick, or about 1 micron to about 10 microns thick. Seed layer thicknesses in the size range of 5 to 20 microns or 10 to 30 microns can be achieved with metal particles having a size of about 1 to 5 microns, or about 10 to 12 microns, or about 10 to 28 microns. Even thicker seed layers can be achieved by applying the seed layer precursor to the base substrate multiple times and / or by using larger metal particles therein.

[0086] In more particular examples, the base substrate may comprise a glass substrate or a ceramic substrate, and the seed layer precursor may comprise a liquid glass binder as a non-conductive matrix material. A suitable liquid glass binder may comprise sodium or potassium silicate in a 40-70% aqueous solution (w / w), optionally including a base (e.g., NaOH, KOH, Ca(OH)2, etc.) and / or alumina particles of 50 nm to 3 microns. The silicate concentration in the aqueous solution may be in the range of 2-50% by weight, or in the range of 2-15% by weight, or in the range of 5-20% by weight, or in the range of 10-30% by weight, or in the range of 15-50% by weight. Organosilanes or organosilanols may also be suitable in this regard.

[0087] In other more specific examples, the base substrate can include a ceramic substrate or a metal substrate, and the seed layer precursor can include a polymer adhesive, such as an epoxy.

[0088] The seed layer as initially deposited (after curing) may be an electrical insulator or have low electrical conductivity due to the lack of interconnection between the metal particles. That is, the seed layer may include a non-conductive seed layer. Surprisingly, the non-conductive seed layer may be converted from an electrical insulator state to an electrical conductor state by mechanical polishing after deposition and curing to form a polished seed layer. Suitable mechanical polishing may be achieved by rubbing the non-conductive seed layer with an abrasive material such as sandpaper or steel wool. In another embodiment, a chemical mechanical polishing process commonly used in the electronics industry may be used instead. Without being bound by theory or mechanism, it is believed that the mechanical polishing process promotes smearing of grains of metal particles in the seed layer to establish interconnections therebetween.

[0089] In addition to promoting electrical conductivity, the physical appearance of the seed layer can be altered after a mechanical polishing operation. For example, Figures 4A and 4B are images of a glass substrate coated with a seed layer containing copper particles before and after polishing, respectively. The initial dull appearance of the seed layer becomes much shinier after polishing. Figure 5 is an image of a metallized glass substrate that can be prepared as described in more detail below.

[0090] The sheet resistance in the polished seed layer can be about 500 mOhm / sq or less, or about 400 mOhm / sq or less, or about 300 mOhm / sq or less, or about 200 mOhm / sq or less, or about 100 mOhm / sq for seed layer thicknesses of about 30 microns or more. At thicknesses of 10 microns or less, the sheet resistivity can be in the range of about 1-10 ohms / sq. A copper-containing seed layer having a sheet resistivity of about 100 mOhm / sq is still about 100 times higher than the sheet resistance of bulk copper, but is still significantly more conductive than conventional materials that are not subjected to mechanical polishing.

[0091] In non-limiting examples, the metal layer deposited on the polished seed layer may have a sheet resistivity of about 1 mOhm / sq or less, or about 0.5 mOhm / sq, or about 0.25 mOhm / sq. For example, a copper-based metal layer may have a sheet resistivity of about 0.15 mOhm / sq for a 300 micron thick layer and about 0.05 mOhm / sq for a 650 micron thick layer.

[0092] Advantageously, the seed layer precursor used herein can be applied to a base substrate and subjected to curing without taking the precaution of an inert atmosphere. Depending on the type of non-conductive matrix material used in the seed layer precursor, curing on the base substrate can occur at a variety of temperatures. In a non-limiting example, sufficient curing of the liquid glass matrix can occur at temperatures up to about 100°C, such as from about 90°C to about 100°C, over a cure time of approximately 10 to 15 minutes. In contrast, the polymer adhesive can be cured at temperatures up to about 250°C, although this temperature can vary considerably depending on the type of epoxy resin used.

[0093] After mechanical polishing (optionally so that the seed layer is rendered electrically conductive), a metal layer can be deposited on the polished seed layer using a metal nanoparticle composition. The metal nanoparticle composition can be formulated to facilitate the selected deposition method, ranging from a low viscosity dispersion suitable for spraying, printing, stenciling, or similar applications, to a thick paste suitable for brush-on, doctor blading, or wipe-on applications for depositing thicker metal layers. The metal layer can be a continuous metallization layer similar to a bulk copper sheet adhered to the base substrate via a seed layer, or metal traces can be directly printed in the desired pattern using a metal nanoparticle composition onto the polished seed layer. Optionally, the continuous metallization layer deposited as described above can be partially etched away to define metal traces on the base substrate. Bond pads at desired locations on the base substrate can be formed by etching or direct printing using a metal nanoparticle composition as well. As shown above, the suitable metal nanoparticle compositions described above can further characterize the CTE match with the base substrate coated according to the disclosure herein. Additionally, alternatively, conventional electroplating or electroless plating techniques may be utilized to similarly form a continuous metallization layer over the polished seed layer.

[0094] In some embodiments, forming a metal layer using a metal nanoparticle composition on the polished seed layer can include a hot pressing operation, where at least a portion of the metal nanoparticles in the metal nanoparticle composition undergo consolidation under hot pressing conditions. Exemplary hot pressing conditions can include a temperature of about 200° C. to about 270° C. and a pressure of about 500 psi to about 2500 psi. The hot pressing can be performed for about 30 minutes to about 90 minutes, although longer or shorter times may be suitable.

[0095] The metal in the metallization layer is not particularly limited and can be any metal that bonds favorably to the polished seed layer. In non-limiting examples, the metal in the metal layer can include, but is not limited to, copper, palladium, gold, or silver.

[0096] The thickness of the metal layer (and the resulting conductive traces) can vary over a wide range. In non-limiting examples, the metal layer can be up to about 500 microns thick, such as from about 300 microns to about 500 microns, or from about 100 microns to about 400 microns, or from about 10 microns to about 100 microns.

[0097] The embodiments disclosed herein include those of the following clauses. A. Metallized Substrate. The substrate comprises a base substrate, a seed layer directly adhered to the base substrate, the seed layer being mechanically polished and including a non-conductive matrix material and a plurality of metal particles, optionally the seed layer being electrically conductive, and a metal layer formed on at least a portion of the seed layer. Optionally, the metal layer may be CTE matched to the base substrate. B. A Process for Metallizing a Base Substrate The process includes providing a base substrate, applying a seed layer material to the base substrate, the seed layer material including a matrix material and a plurality of metal particles, curing the seed layer material on the base substrate to form a non-conductive seed layer adhered to the base substrate, mechanically polishing the non-conductive seed layer to form a polished seed layer, optionally the polished seed layer being electrically conductive, and forming a metal layer on at least a portion of the polished conductive seed layer. An interposer, interconnect, packaging substrate, or chip that includes a metallized substrate of CA. An interposer comprising a DA metallized substrate, the base substrate comprising aluminum nitride or silicon nitride, and the non-conductive matrix material comprising a liquid glass binder or a polymer adhesive.

[0098] Embodiments AC may have one or more of the following additional elements in any combination. Element 1: The base substrate comprises ceramic, polymer, silicon, or glass. Element 2: The base substrate comprises a ceramic selected from the group consisting of aluminum nitride, silicon nitride, indium tin oxide, and any combination thereof. Element 3: The non-conductive matrix includes a material formed from a liquid glass binder, a polymer adhesive, or any combination thereof. Element 4: The base substrate comprises a glass or ceramic, and the non-conductive matrix comprises a material formed from a liquid glass binder. Element 5: The base substrate comprises a ceramic or a polymer, and the non-conductive matrix comprises a polymer adhesive. Element 6: The metal particles include copper particles. Element 7: The metal layer comprises copper. Element 8: The metal layer is CTE matched to the base substrate. Element 9: The metal layer includes a continuous metallization layer or one or more metal traces. Element 9A: The metal layer includes one or more conductive traces formed by selective etching of a continuous metallization layer. Element 9B: The metal layer includes one or more conductive traces formed by selectively depositing a metal nanoparticle composition onto a conductive seed layer. Element 10: The conductive seed layer has a thickness in the range of about 500 nm to about 50 microns. Element 11: The metal layer has a thickness of about 100 microns to about 2000 microns. Element 12: Forming a metal layer on the conductive seed layer includes applying a metal nanoparticle composition on the conductive seed layer and consolidating a plurality of metal nanoparticles in the metal nanoparticle composition. Element 13: Consolidating the plurality of metal nanoparticles is performed by a hot pressing operation.

[0099] As a non-limiting example, exemplary combinations applicable to A through D include: 1 or 2, and 3, 4, or 5; 1 or 2, and 6; 1 or 2, and 6 and 7; 1 or 2, and 6; 1 or 2, and 7; 1 or 2, and 6-8; 1 or 2, and 8; 1 or 2, and 9, 9A, or 9B; 1 or 2, and 9 and 9A; 1 or 2, and 9 and 9B; 1 or 2, and 10; 1 or 2, and 11; 1 or 2, and 10 and 11; 3 and 6; 3, and 6 and 7; 3 and 6; 3 and 7; 3, and 6-8; 3 and 8; 3, and 9, 9A, or 9B; 3, and 9 and 9A; 3, and 9 and 9B; 3 and 10; 3 and 11; 3, and 10 and 11; 4 or 5, and 6; 4 or 5, and 6 and 7; 4 or 5, and 6; 4 or Examples include, but are not limited to, 5, and 7; 4 or 5, and 6-8; 4 or 5, and 8; 4 or 5, and 9, 9A, or 9B; 4 or 5, and 9 and 9A; 4 or 5, and 9 and 9B; 4 or 5, and 10; 4 or 5, and 11; 4 or 5, and 10 and 11; 6 and 7; 6, 7 and 8; 6 and 8; 6, and 9, 9A, or 9B; 6, and 9 and 9A; 6, and 9 and 9B; 6 and 10; 6 and 11; 6, and 10 and 11; 7 and 8; 7, and 9, 9A, or 9B; 7, and 9 and 9A; 7, and 9 and 9B; 7 and 10; 7 and 11; 7, and 10 and 11; 9 and 9A, and 10; 9 and 9A, and 11; 9 and 9B, and 10; 9 and 9B, and 11; 10 and 11. 13 and / or 14 may be further combined with any of the above.

[0100] This disclosure is further subject to the following non-limiting provisions. Clause 1. A metallized substrate, A base material; a seed layer directly adhered to a base substrate, the seed layer being mechanically polished to form a polished seed layer, the seed layer comprising a non-conductive matrix material and a plurality of metal particles, optionally the polished seed layer being electrically conductive; and a metal layer formed on at least a portion of the polished seed layer. Clause 2. The metallized substrate of clause 1, wherein the base substrate comprises a ceramic, a polymer, a silicon, or a glass. Clause 3. The metallized substrate of clause 2, wherein the base substrate comprises a ceramic selected from the group consisting of aluminum nitride, silicon nitride, indium tin oxide, and any combination thereof. Clause 4. The metallized substrate of any one of clauses 1-3, wherein the non-conductive matrix material comprises a material formed from a liquid glass binder, a polymer adhesive, or any combination thereof. Clause 5. The metallized substrate of clause 1 or 4, wherein the base substrate comprises glass or ceramic and the non-conductive matrix material comprises a material formed from a liquid glass binder. Clause 6. The metallized substrate of clause 1 or 4, wherein the base substrate comprises a ceramic or a polymer and the non-conductive matrix material comprises a polymer adhesive. Clause 7. The metallized substrate of any one of clauses 1 to 6, wherein the metal particles comprise copper particles. Clause 8. The metallized substrate of clause 7, wherein the metal layer comprises copper. Clause 9. The metallized substrate of any one of clauses 1-8, wherein the metal layer is CTE matched to the base substrate. Clause 10. The metallized substrate of any one of clauses 1-9, wherein the metal layer comprises a continuous metallization layer or one or more metal traces. Clause 11. The metallized substrate of any one of clauses 1-10, wherein the seed layer has a thickness in the range of about 500 nm to about 50 microns. Clause 12. The metallized substrate of any one of clauses 1-11, wherein the metal layer has a thickness in the range of about 100 microns to about 2000 microns. Clause 13. An interposer comprising the metallized substrate of any one of clauses 1-12, wherein the base substrate comprises aluminum nitride or silicon nitride, and the non-conductive matrix material comprises a material formed from a liquid glass binder or a polymer adhesive. Clause 14. A process Providing a base substrate; a seed layer precursor on a base substrate, applying a seed layer precursor, the seed layer precursor including a non-conductive matrix material and a plurality of metal particles; curing a seed layer precursor on the base substrate to form a non-conductive seed layer adhered to the base substrate; mechanically polishing the non-conductive seed layer to form a polished seed layer, optionally the polished seed layer being electrically conductive; forming a metal layer on at least a portion of the polished seed layer. Clause 15. Forming a metal layer on at least a portion of the polished seed layer comprises: applying a metal nanoparticle composition onto the polished seed layer; and consolidating the plurality of metal nanoparticles within the metal nanoparticle composition. Clause 16. The method of clause 15, wherein consolidating the plurality of metal nanoparticles is performed by a hot pressing operation. Clause 17. The method of any one of clauses 14 to 16, wherein the base substrate comprises a ceramic, a polymer, a silicon, or a glass. Clause 18. The method of clause 17, wherein the base substrate comprises a ceramic selected from the group consisting of aluminum nitride, silicon nitride, indium tin oxide, and any combination thereof. Clause 19. The method of any one of clauses 14-18, wherein the non-conductive matrix material comprises a material formed from a liquid glass binder, a polymer adhesive, or any combination thereof. Clause 20. The method of any one of clauses 14 to 19, wherein the metal particles comprise copper particles. Clause 21. The method of clause 20, wherein the metal layer comprises copper. Clause 22. The method of any one of clauses 14 to 21, wherein the metal layer comprises a continuous metallization layer or one or more conductive traces. Clause 23. The method of clause 22, wherein the metal layer comprises one or more conductive traces formed by selective etching of a continuous metallization layer. Clause 24. The method of clause 22, wherein the metal layer comprises one or more conductive traces formed by selectively depositing a metal nanoparticle composition onto the polished seed layer. Clause 25. The method of any one of clauses 14 to 24, wherein the metal particles comprise micron-sized metal particles, metal nanoparticles, or any combination thereof.

[0101] One or more exemplary embodiments incorporating features of the present disclosure are presented herein. For the sake of clarity, not all features of a physical implementation are described or illustrated in this application. It should be understood that in developing a physical embodiment incorporating the present disclosure, numerous implementation-specific decisions must be made to achieve the developer's goals, such as compliance with system-related constraints, business-related constraints, government-related constraints, and other constraints that vary from implementation to implementation and from time to time. Although the developer's efforts may require significant time, such efforts would nevertheless be routine for those skilled in the art and who have the benefit of the present disclosure.

[0102] Thus, the present disclosure is well adapted to attain the ends and advantages mentioned, as well as those inherent therein. The particular embodiments disclosed above are illustrative only, as the disclosure may be modified and practiced in different but equivalent manners apparent to those skilled in the art having the benefit of the teachings herein. Moreover, no limitations are intended to the details of construction or design shown herein, other than as described in the following claims. It is therefore apparent that the specific exemplary embodiments disclosed above may be altered, combined or modified, and all such variations are deemed to be within the scope and spirit of the invention. The disclosure herein may suitably be practiced in the absence of optional elements not specifically disclosed herein and / or optional elements disclosed herein. Although the compositions and methods are described in terms "comprising," "containing," or "including" various components or steps, the compositions and methods may also "consist essentially of" or "consist of" the various components and steps. All of the numbers and ranges disclosed above may be varied by some amount. Whenever a numerical range is disclosed with a lower and upper limit, any number falling within that range and any range encompassed therein are specifically disclosed. In particular, all ranges of values ​​disclosed herein (in the form of "from about a to about b," or equivalently, "from approximately a to b," or equivalently, "from approximately a to b") are to be understood to describe all numbers and ranges encompassed within the broader range of values. Additionally, the terms in the claims have their plain and ordinary meaning unless expressly and unambiguously defined by the patent owner. Additionally, the indefinite article "a" or "an," as used in the claims, is defined herein to mean one or more of the element it introduces.

Claims

1. A metallized substrate, A base material; a seed layer directly adhered to the base substrate, the seed layer being mechanically polished to form a polished seed layer, the seed layer comprising a non-conductive matrix material and a plurality of metal particles, optionally the polished seed layer being electrically conductive; and a metal layer formed on at least a portion of the polished seed layer.

2. The metallized substrate of claim 1 , wherein the base substrate comprises a ceramic, a polymer, a silicon, or a glass.

3. 3. The metallized substrate of claim 2, wherein the base substrate comprises a ceramic selected from the group consisting of aluminum nitride, silicon nitride, indium tin oxide, and any combination thereof.

4. The metallized substrate of claim 1 , wherein the non-conductive matrix material comprises a material formed from a liquid glass binder, a polymer adhesive, or any combination thereof.

5. The metallized substrate of claim 1 , wherein the base substrate comprises a glass or ceramic, and the non-conductive matrix material comprises a material formed from a liquid glass binder.

6. The metallized substrate of claim 1 , wherein the base substrate comprises a ceramic or a polymer, and the non-conductive matrix material comprises a polymer adhesive.

7. The metallized substrate of claim 1 , wherein the metal particles comprise copper particles.

8. The metallized substrate of claim 7 , wherein the metal layer comprises copper.

9. The metallized substrate of claim 1 , wherein the metal layer is CTE-matched to the base substrate.

10. The metallized substrate of claim 1 , wherein the metal layer comprises a continuous metallization layer or one or more metal traces.

11. The metallized substrate of claim 1 , wherein the seed layer has a thickness ranging from about 500 nm to about 50 microns.

12. The metallized substrate of claim 1 , wherein the metal layer has a thickness ranging from about 100 microns to about 2000 microns.

13. 13. An interposer comprising the metallized substrate of claim 1, wherein the base substrate comprises aluminum nitride or silicon nitride, and the non-conductive matrix material comprises a material formed from a liquid glass binder or a polymer adhesive.

14. A process comprising: Providing a base substrate; a seed layer precursor on the base substrate, applying a seed layer precursor, the seed layer precursor comprising a non-conductive matrix material and a plurality of metal particles; curing the seed layer precursor on the base substrate to form a non-conductive seed layer adhered to the base substrate; mechanically polishing the non-conductive seed layer to form a polished seed layer, optionally the polished seed layer being electrically conductive; forming a metal layer over at least a portion of the polished seed layer.

15. forming the metal layer on at least a portion of the polished seed layer comprises: applying a metal nanoparticle composition onto the polished seed layer; and consolidating the plurality of metal nanoparticles within the metal nanoparticle composition.

16. The method of claim 15 , wherein consolidating the plurality of metallic nanoparticles is performed by a hot pressing operation.

17. The method of claim 14 , wherein the base substrate comprises a ceramic, a polymer, a silicon, or a glass.

18. 20. The method of claim 17, wherein the base substrate comprises a ceramic selected from the group consisting of aluminum nitride, silicon nitride, indium tin oxide, and any combination thereof.

19. The method of claim 14 , wherein the non-conductive matrix material comprises a material formed from a liquid glass binder, a polymer adhesive, or any combination thereof.

20. The method of claim 14 , wherein the metal particles comprise copper particles.

21. The method of claim 20 , wherein the metal layer comprises copper.

22. The method of claim 14 , wherein the metal layer comprises a continuous metallization layer or one or more conductive traces.

23. 23. The method of claim 22, wherein the metal layer comprises one or more conductive traces formed by selective etching of the continuous metallization layer.

24. 23. The method of claim 22, wherein the metal layer comprises one or more conductive traces formed by selectively depositing a metal nanoparticle composition onto the polished seed layer.

25. The method of claim 14 , wherein the metal particles comprise micron-sized metal particles, metal nanoparticles, or any combination thereof.